Application of self-assembled hydrogel in occluding hypersensitive dentinal tubules
Through self-assembly hydrogel technology, cross-linked hydrogel is formed by contact between macromolecules and polyphenols, and it penetrates into the internal dentin tubes to seal, solving the problems of insufficient sealing depth and easy material fall off in the existing technology, realizing the Stable and durable dentin tubular sealing.
Patent Information
- Application Number
- CN202311565841.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-22
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-11-22
AI Technical Summary
The existing desensitized materials used to seal dentin tubules have insufficient sealing depth, which leads to the problem of easy material falling off.
Self-assembled hydrogel is formed by contacting 1-30% w/w macromolecular solution with 1-30% w/w polyphenol solution, and dense crosslinked large Molecular hydrogel, penetrates deep into the dentin tubules and seals them.
Deep sealing of dentin tubules is achieved, the stability and durability of sealing are improved, and the problem of easy material falls off is avoided. At the same time, it has the advantages of low cost and controllability of glue formation.
Smart Images

Figure CN117598908B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of dental biomaterials, and in particular relates to the use of a self-assembled hydrogel in blocking hypersensitive dentinal tubules. Background Art
[0002] Dentin hypersensitivity is a common clinical symptom. It is a disease that causes short-term or sharp pain on the surface of dentin due to temperature, chemical and mechanical stimulation. Among them, the fluid dynamics theory believes that dentin hypersensitivity is caused by the exposure of dentinal tubules. External stimulation acting on the surface of dentin causes the fluid in the dentinal tubules to flow in multiple directions and transmit to the pulp tissue, thereby causing the pulp nerve fibers to become excited and produce pain. Therefore, dentin hypersensitivity can be treated by blocking the hypersensitive dentinal tubules.
[0003] The prior art with application number CN2017107874575 discloses a material for blocking dentinal tubules to desensitize teeth. After carboxymethyl chitosan and lysozyme form a nanogel, phosphate ions and calcium ions are introduced to form a carboxymethyl chitosan-lysozyme-amorphous calcium phosphate nanocomposite, so that the prepared desensitizing material can penetrate into the dentinal tubules and block the inside and surface of the dentinal tubules, thereby achieving rapid desensitization and firm bonding with the tooth surface.
[0004] However, the existing desensitizing materials used to seal dentinal tubules generally cure and seal after applying a composite cross-linked macromolecular gel solution to dentin. Due to the small diameter of dentinal tubules, it is difficult for the composite cross-linked macromolecular gel solution to penetrate deep into the dentinal tubules, resulting in insufficient sealing depth of the dentinal tubules and a prominent problem of easy falling off of the desensitizing material. Summary of the invention
[0005] The present application discloses the use of a self-assembled hydrogel in plugging hypersensitive dentinal tubules, aiming to solve the technical problem of insufficient plugging depth of the desensitizing material used for plugging dentinal tubules as mentioned in the background above.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a use of a self-assembled hydrogel. The use described in the present application is the use of the self-assembled hydrogel for preparing a hypersensitive dentin tubule plugging agent;
[0007] The self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution.
[0008] In some embodiments of the first aspect, the macromolecular compound in the macromolecular solution is one or a mixture of silk fibroin, polyvinyl alcohol, polyvinyl pyrrolidone and derivatives thereof.
[0009] In some embodiments of the first aspect, the polyphenols in the polyphenol solution are one or a mixture of tannic acid, ellagic acid, epigallocatechin gallate, proanthocyanidins, gallic acid, and pyrogallic acid.
[0010] In some embodiments of the first aspect, when the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is (0.5-15):1.
[0011] The second aspect of the present application provides a desensitizing agent for treating dentin hypersensitivity. The desensitizing agent for treating dentin hypersensitivity of the present application comprises a self-assembling hydrogel;
[0012] The self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution.
[0013] In some embodiments of the second aspect, the macromolecular compound in the macromolecular solution is one or a mixture of silk fibroin, polyvinyl alcohol, polyvinyl pyrrolidone and derivatives thereof.
[0014] In some embodiments of the second aspect, the polyphenols in the polyphenol solution are one or a mixture of tannic acid, ellagic acid, epigallocatechin gallate, proanthocyanidins, gallic acid, and pyrogallic acid.
[0015] In some embodiments of the second aspect, when the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is (0.5-15):1.
[0016] A third aspect of the present application provides a method for blocking hypersensitive dentinal tubules, the method comprising: applying the desensitizing therapeutic agent for dentin hypersensitivity described in the present application to the surface of hypersensitive dentin.
[0017] In some embodiments of the third aspect, the method of applying the desensitizing therapeutic agent for dentin hypersensitivity to the surface of hypersensitive dentin comprises:
[0018] After releasing the macromolecular solution on the surface of the hypersensitive dentin and air-drying it, releasing the polyphenol solution on the surface of the hypersensitive dentin and air-drying it;
[0019] There is no limitation on the release order of the macromolecular solution and the polyphenol solution.
[0020] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0021] The first aspect of the present application provides a use of a self-assembled hydrogel for preparing a hypersensitive dentinal tubule plugging agent. Among them, based on the self-assembled hydrogel of the present application, a 1-30% w / w macromolecular solution is contacted with a 1-30% w / w polyphenol solution to form a self-assembled hydrogel component solution of the present application. Therefore, one of the component solutions of the self-assembled hydrogel of the present application can be applied to the surface of the hypersensitive dentin successively, so that the macromolecular solution and the polyphenol solution respectively penetrate into the deep layer of the dentinal tubules and self-assemble inside the dentinal tubules to form a dense cross-linked macromolecular hydrogel, effectively avoiding the problem that the composite cross-linked macromolecular gel solution is difficult to penetrate into the deep layer of the dentinal tubules, and the deep plugging of the hypersensitive dentinal tubules is achieved, and the cross-linked macromolecular hydrogel formed by self-assembly can be stably engaged inside the dentinal tubules and is not easy to fall off; in addition, the self-assembled hydrogel of the present application has simple components, easy-to-obtain raw materials, and does not contain any adjuvants and chemical reactions, and has the advantages of low cost and high gel controllability.
[0022] The second aspect of the present application provides a desensitizing therapeutic agent for dentin hypersensitivity, which contains a self-assembled hydrogel. Therefore, when the desensitizing therapeutic agent for dentin hypersensitivity of the present application is used for the treatment of dentin hypersensitivity, the macromolecular solution and the polyphenol solution can respectively penetrate into the deep layer of the dentinal tubules and self-assemble inside the dentinal tubules to form a dense cross-linked macromolecular hydrogel, thereby achieving deep blocking of the allergic dentinal tubules to achieve desensitization of dentin hypersensitivity, and the cross-linked macromolecular hydrogel formed by self-assembly can be stuck inside the dentinal tubules and is not easy to fall off. Among them, the test results of the embodiment show that the desensitizing therapeutic agent for dentin hypersensitivity provided by the present application can achieve blocking of dentinal tubules with a depth of more than 250μm within one hour. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 Surface and cross-sectional SEM images (magnified 5000 times) of a blank group with simulated dentin hypersensitivity and an experimental group with SF-TA self-assembled hydrogel blocking dentin tubules provided in the embodiments of the present application, wherein A1 is a surface SEM image of the blank group with simulated dentin hypersensitivity, A2 is a cross-sectional SEM image of the blank group with simulated dentin hypersensitivity, B1 is a surface SEM image of the experimental group with SF-TA self-assembled hydrogel blocking dentin tubules, and B2 is a cross-sectional SEM image of the experimental group with SF-TA self-assembled hydrogel blocking dentin tubules;
[0025] Figure 2This is a cross-sectional SEM image of the SF-TA self-assembled hydrogel occluding dentin tubules experimental group provided in the examples of the present application (magnified 1000 times);
[0026] Figure 3 A bar graph showing the bursting data of SF-TA self-assembled hydrogel blocking dentin tubules provided in an embodiment of the present application;
[0027] Figure 4 Surface and cross-sectional SEM images (magnified 5000 times) of TA-SF hydrogel blocking dentin tubules provided in the examples of the present application;
[0028] Figure 5 Surface and cross-sectional SEM images of the dentinal tubules of the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules and the dentinal tubules of SF-TA self-assembled hydrogel blocked dentinal tubules and treated with brushing teeth after pH cycling for 21 days provided in the embodiments of the present application, wherein A1 is the surface SEM image of the dentinal tubules of the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules after pH cycling for 21 days, and A2 is the cross-sectional SEM image of the dentinal tubules of the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules after pH cycling for 21 days; B1 is the surface SEM image of the dentinal tubules of SF-TA self-assembled hydrogel blocked dentinal tubules and treated with brushing teeth after pH cycling for 21 days, and B2 is the cross-sectional SEM image of the dentinal tubules of SF-TA self-assembled hydrogel blocked dentinal tubules and treated with brushing teeth after pH cycling for 21 days;
[0029] Figure 6 A bar graph showing the bursting data of the SF-TA self-assembled hydrogel for blocking dentinal tubules provided in the examples of the present application and the SF-TA self-assembled hydrogel for blocking dentinal tubules and brushing the dentinal tubules after pH cycling for 21 days;
[0030] Figure 7 A bar graph showing the cell proliferation rate of the dentin slice treated with the SF-TA self-assembled hydrogel provided in the embodiment of the present application after co-culture with dental pulp cells in the improved TDD device;
[0031] Figure 8Surface and cross-sectional SEM images of the in vivo dentinal tubules experimental group of rats before and after the SF-TA self-assembled hydrogel blocked the dentinal tubules provided in the embodiments of the present application, wherein A1 is the surface SEM image of the in vivo dentinal tubules experimental group of rats before the SF-TA self-assembled hydrogel blocked the dentinal tubules, A2 is the cross-sectional SEM image of the in vivo dentinal tubules experimental group of rats before the SF-TA self-assembled hydrogel blocked the dentinal tubules, B1 is the surface SEM image of the in vivo dentinal tubules experimental group of rats after the SF-TA self-assembled hydrogel blocked the dentinal tubules, and B2 is the cross-sectional SEM image of the in vivo dentinal tubules experimental group of rats after the SF-TA self-assembled hydrogel blocked the dentinal tubules;
[0032] Fig. 9 A bar graph showing the microhardness of a dentin sheet treated with the SF-TA self-assembled hydrogel provided in an embodiment of the present application after being in the oral cavity of a rat for 21 days;
[0033] Fig.10 The surface and cross-sectional SEM images of the dentinal tubules of the SF-TA self-assembled hydrogel provided in the embodiment of the present application before and after being used in rabbit teeth, wherein A1 is the surface SEM image of the dentinal tubules before the SF-TA self-assembled hydrogel is used in rabbit teeth, A2 is the cross-sectional SEM image of the dentinal tubules before the SF-TA self-assembled hydrogel is used in rabbit teeth, B1 is the surface SEM image of the dentinal tubules after the SF-TA self-assembled hydrogel is used in rabbit teeth, and B2 is the cross-sectional SEM image of the dentinal tubules after the SF-TA self-assembled hydrogel is used in rabbit teeth;
[0034] Fig.11 Surface and cross-sectional SEM images of a blank group simulating dentin hypersensitivity and a PVA-TA self-assembled hydrogel occluding dentin tubules experimental group provided in the examples of the present application;
[0035] Fig.12 A bar graph showing the bursting data of the PVA-TA self-assembled hydrogel for blocking dentin tubules provided in the examples of the present application;
[0036] Fig.13 A bar graph showing the burst data of the PVP-TA self-assembled hydrogel for blocking dentin tubules provided in the examples of the present application;
[0037] Fig.14 A bar graph showing the burst data of the PVP-GA self-assembled hydrogel blocking dentin tubules provided in the examples of the present application;
[0038] Fig.15 This is a bar graph of the bursting data of the PVP-GA self-assembled hydrogel blocking dentin tubules provided in the examples of the present application. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.
[0041] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0042] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0043] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0044] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be understood as each intermediate value between the upper and lower limits of the scope also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.
[0045] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0046] In a first aspect, the present application provides a use of a self-assembled hydrogel, wherein the self-assembled hydrogel is used to prepare a hypersensitive dentin tubule plugging agent, wherein the self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution.
[0047] It should be noted that the dentinal tubule plugging agent refers to a preparation having good antibacterial and antimicrobial functions and unique permeability, which can be tightly combined with the allergic dentin bonding surface to block the allergic dentinal tubules and play a desensitizing role.
[0048] It should be noted that when the 1-30% w / w macromolecular solution is in contact with the 1-30% w / w polyphenol solution, the mass concentrations of the macromolecular solution and the polyphenol solution may be the same or different. For example, the mass concentration of the macromolecular solution may be 1% w / w, 5% w / w, 10% w / w, 15% w / w, 20% w / w, 25% w / w, 30% w / w, or any mass concentration within the mass concentration range; the mass concentration of the polyphenol solution may be 1% w / w, 5% w / w, 10% w / w, 15% w / w, 20% w / w, 25% w / w, 30% w / w, or any mass concentration within the mass concentration range.
[0049] Based on the above description, it can be seen that the embodiment of the present application provides a self-assembled hydrogel for the preparation of a hypersensitive dentinal tubule plugging agent, and the self-assembled hydrogel of the present application is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution. Therefore, when one of the component solutions of the self-assembled hydrogel of the present application is applied to the surface of hypersensitive dentin in sequence, the macromolecular solution and the polyphenol solution can penetrate into the deep layer of the hypersensitive dentinal tubules and self-assemble inside the dentinal tubules to form a dense cross-linked macromolecular hydrogel, thereby effectively avoiding the problem that the composite cross-linked macromolecular gel solution is difficult to penetrate into the deep layer of the dentinal tubules, achieving deep plugging of the dentinal tubules and desensitization of dentin hypersensitivity, and the cross-linked macromolecular hydrogel formed by self-assembly can be stably engaged in the interior of the dentinal tubules and is not easy to fall off; in addition, the self-assembled hydrogel of the present application has simple components, easy-to-obtain raw materials, and does not contain any adjuvants and chemical reactions, and has the advantages of low cost and high gel controllability.
[0050] In a specific embodiment, the macromolecular compound in the macromolecular solution is preferably one or a mixture of silk fibroin, polyvinyl alcohol, polyvinyl pyrrolidone and derivatives thereof, wherein these macromolecular compounds have good biocompatibility and cross-linking activity, can be gently contacted with the polyphenol solution and efficiently self-assembled to form a cross-linked macromolecular hydrogel, without the need to introduce chemical reagents, and are safe and reliable.
[0051] In a specific embodiment, the polyphenols in the polyphenol solution are preferably one or a mixture of tannic acid, ellagic acid, epigallocatechin gallate, proanthocyanidin, gallic acid, and pyrogallic acid. These polyphenol solutions have good biocompatibility and cross-linking activity, can be gently contacted with macromolecular solutions and efficiently self-assembled to form cross-linked macromolecular hydrogels, without the need to introduce chemical reagents, and are safe and reliable; at the same time, these polyphenol solutions have excellent antibacterial activity and can effectively inhibit various Gram-positive and Gram-negative bacteria.
[0052] In a specific embodiment, when the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is preferably (0.5-15): 1. The mass ratio of the macromolecular solution to the polyphenol solution may be (0.5: 1), (1: 1), (5: 1), (10: 1), (15: 1) or any ratio within the mass ratio range.
[0053] In a second aspect, the present invention provides a desensitizing agent for dentin hypersensitivity. The desensitizing agent for dentin hypersensitivity of the present invention contains a self-assembled hydrogel, wherein the self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution.
[0054] In a specific embodiment, the macromolecular compound in the macromolecular solution is preferably one or a mixture of silk fibroin, polyvinyl alcohol, polyvinyl pyrrolidone and derivatives thereof. Among them, these macromolecular compounds have good biocompatibility and cross-linking activity, can be gently contacted with the polyphenol solution and efficiently self-assembled to form macromolecular cross-linked hydrogels to block dentinal tubules, and quickly achieve desensitization treatment for dentin hypersensitivity without the introduction of chemical reagents, which is safe and reliable with good treatment effect.
[0055] In a specific embodiment, the polyphenols in the polyphenol solution are preferably one or a mixture of tannic acid, ellagic acid, epigallocatechin gallate, proanthocyanidin, gallic acid, and pyrogallic acid. These polyphenol solutions have good biocompatibility and cross-linking activity, can be gently contacted with macromolecular solutions and efficiently self-assembled to form cross-linked macromolecular hydrogels, without the need to introduce chemical reagents, and are safe and reliable; at the same time, these polyphenol solutions have excellent antibacterial activity and can effectively inhibit various Gram-positive and Gram-negative bacteria.
[0056] In a specific embodiment, when the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is preferably (0.5-15): 1. The mass ratio of the macromolecular solution to the polyphenol solution may be (0.5: 1), (1: 1), (5: 1), (10: 1), (15: 1) or any ratio within the mass ratio range.
[0057] In a third aspect, an embodiment of the present application provides a method for blocking hypersensitive dentinal tubules, the method preferably comprising: applying the desensitizing therapeutic agent for dentin hypersensitivity described in the present application to the surface of the hypersensitive dentin.
[0058] In a specific embodiment, the method of applying the desensitizing agent for dentin hypersensitivity to the surface of hypersensitive dentin comprises:
[0059] After releasing the macromolecular solution on the surface of the hypersensitive dentin and air-drying it, releasing the polyphenol solution on the surface of the hypersensitive dentin and air-drying it;
[0060] There is no limitation on the release order of the macromolecular solution and the polyphenol solution.
[0061] It should be noted that the specific method of applying the desensitizing agent for dentin hypersensitivity to the surface of hypersensitive dentin includes:
[0062] After releasing the macromolecular solution on the surface of the hypersensitive dentin and air-drying it, releasing the polyphenol solution on the surface of the hypersensitive dentin and air-drying it;
[0063] Alternatively, after the polyphenol solution is released on the surface of the hypersensitive dentin and air-dried, the macromolecular solution is released on the surface of the hypersensitive dentin and air-dried.
[0064] The embodiment of the present application releases a macromolecular solution or a polyphenol solution to the surface of the hypersensitive dentin and air-dries it, and then releases a polyphenol solution or a macromolecular solution to the surface of the hypersensitive dentin and air-dries it, so that the self-assembly component solutions released twice can fully penetrate into the deep layer of the dentinal tubules and self-assemble to form a cross-linked macromolecular hydrogel, thereby achieving deep blocking of the dentinal tubules and achieving desensitization treatment of dentin hypersensitivity, which is convenient, fast and has a good therapeutic effect.
[0065] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0066] Example 1
[0067] This embodiment provides a use of SF-TA self-assembled hydrogel, specifically including:
[0068] Preparation of S101-TA solution
[0069] Add 10 g of tannic acid (TA) powder into 90 g of deionized water and stir to dissolve to obtain a 10% TA solution for later use;
[0070] Preparation of S102-SF solution
[0071] Add 63.6 g of Na2CO3 powder into 30 L of deionized water and stir to dissolve to obtain a 0.02 M Na2CO3 solution for later use;
[0072] Add 80.77 g of LiBr powder into 100 mL of deionized water and stir to dissolve to obtain a 9.3 M LiBr solution for later use;
[0073] 300 g of a molecular weight of 2 × 10 4 Da polyethylene glycol (PEG) powder was added into 1700 g of deionized water and stirred for 2 h to obtain a PEG solution with a mass fraction of 15%, which was set aside;
[0074] 120 g of natural silk cocoons were soaked in 10 L of the above Na2CO3 solution, boiled for 1 hour, the cocoons were taken out and the liquid was discarded, and this step was repeated 3 times. After the silk was washed by boiling 3 times, the water was wrung out, and then spread on tin foil and dried at 40°C overnight to obtain degummed silk.
[0075] The degummed silk was dissolved in 100 mL of the above LiBr solution in a water bath at 60°C with stirring, and the resulting solution was dialyzed with deionized water for 3 days (the molecular weight of the dialysis bag was 141.4×10 4 Da), and finally the PEG solution was reverse dialyzed for 1 day to obtain a 10% SF solution for standby use.
[0076] S103-Simulation of dentin hypersensitivity
[0077] The dentin part of the excised tooth was cut with a tooth cutter in a direction perpendicular to the long axis of the tooth to obtain a dentin slice with a thickness of about 1 mm, which was gradually polished with 600-3000# sandpaper and then washed with deionized water. Then, 17% EDTA with pH=7 was used for acid etching for 8 minutes to expose the dentinal tubules, and then immersed in deionized water for ultrasonication 3 times, each time for 5 minutes.
[0078] S104-Oil sealing treatment for dentin hypersensitivity
[0079] After drying the dentin slice with nitrogen, the SF solution was first added to the dentin slice and air-dried for about 30 minutes, and then the TA solution was added to the surface of the dentin slice and air-dried again. Finally, the residue on the surface of the dentin slice was cleaned with an electric toothbrush.
[0080] In order to verify the technical effect of Example 1, the dentin treated with SF-TA self-assembled hydrogel was subjected to structural characterization and performance testing, as follows:
[0081] 1.1 Characterization of dentin surface and cross-section morphology
[0082] After the dentin slices treated with SF-TA self-assembled hydrogel and liquid nitrogen-fractured dentin slices were dried overnight in a drying box, the microscopic morphology of the surface and cross-section of the dentin slices was characterized using a scanning electron microscope (accelerating voltage of 10.00 kV). Figure 1 to Figure 2 As shown. Among them, Figure 1 Surface and cross-sectional SEM images (magnified 5000 times) of the blank group simulating dentin hypersensitivity and the experimental group of SF-TA self-assembled hydrogel blocking dentin tubules. Specifically, Figure 1 -A1 is the surface SEM image of the blank group simulating dentin hypersensitivity, Figure 1 -A2 is the cross-sectional SEM image of the blank group simulating dentin hypersensitivity, Figure 1 -B1 is the surface SEM image of the experimental group of SF-TA self-assembled hydrogel blocking dentin tubules, Figure 1 -B2 is the cross-sectional SEM image of the experimental group of SF-TA self-assembled hydrogel blocking dentin tubules; Figure 2 This is the cross-sectional SEM image of the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules (magnified 1000 times).
[0083] according to Figure 1 It can be seen that compared with the blank group of simulated dentin hypersensitivity, the dentin slices treated with SF-TA self-assembled hydrogel formed a strict occlusion of dentinal tubules; at the same time, Figure 2 It shows that the plugging depth of SF-TA self-assembled hydrogel exceeds 250 μm.
[0084] 1.2 Explosion experiment to test the blocking performance of SF-TA self-assembled hydrogel in blocking dentinal tubules
[0085] The sealing performance of SF-TA self-assembled hydrogel on dentin slices with dentin hypersensitivity was tested by using a blasting device: first, the dentin slice treated with SF-TA self-assembled hydrogel was clamped between a pair of rubber rings with a central opening and fixed in the device. Secondly, when the gas passes through, the water droplets will move in the tube, and the critical air pressure is recorded at this time. In order to simulate the effects of friction and acid etching in the oral environment, this embodiment subjected the dentin slice to mechanical friction treatment and then conducted a second blasting experiment; finally, the dentin slice was placed in a 2% EDTA aqueous solution for acid etching for 2 minutes, and the sealing performance was tested for the third time using a blasting device. The results were: Figure 3 As shown. Among them, Figure 3 The bar graph shows the bursting data of SF-TA self-assembled hydrogel blocking dentin tubules.
[0086] according to Figure 3 It can be seen that the airtight pressure value treated with SF-TA self-assembled hydrogel can reach the maximum value of 160kPa of the blasting device, and it does not decrease after experiencing mechanical friction and acid etching, maintaining a good sealing state, indicating that SF-TA self-assembled hydrogel has good sealing stability for allergic dentinal tubules.
[0087] 1.3 Exploring the use of SF-TA self-assembled hydrogels
[0088] After the dentin slice was dried with nitrogen, TA solution and SF solution were added to the dentin surface. Specifically, TA solution was first added to the dentin slice and air-dried for about 30 minutes, and then SF solution was added to the dentin slice and air-dried again. The SF-TA self-assembled hydrogel remaining on the surface of the dentin slice was brushed off with an electric toothbrush. The obtained dentin slice was observed by scanning electron microscopy, and the results were Figure 4 As shown in the figure, the surface and cross-sectional SEM images of TA-SF hydrogel blocking dentin tubules (magnified 5000 times).
[0089] Will Figure 4 and Figure 1 In comparison, it can be seen that the plugging effect of SF-TA self-assembled hydrogel is better than that of TA-SF self-assembled hydrogel.
[0090] 1.4 pH cycle test of the long-term effect of SF-TA self-assembled hydrogel on dentin sealing
[0091] 0.1665 g of CaCl2, 0.1224 g of KH2PO4, 19.689 g of KCl, 4.7669 g of HEPES buffer and 0.06 g of NaN3 were dissolved in 1 L of deionized water, and the pH was adjusted to 7.0 using NaOH solution to obtain simulated artificial saliva. 0.3329 g of CaCl2, 0.408 g of KH2PO4 and 3.0026 g of acetic acid were dissolved in 1 L of deionized water, and the pH was adjusted to 4.8 using NaOH solution to obtain simulated demineralized solution.
[0092] In order to verify the long-term effectiveness of SF-TA self-assembled hydrogel treatment, the dentin slices treated with SF-TA self-assembled hydrogel were immersed in the above-mentioned simulated artificial saliva for 8 hours, and immersed in the above-mentioned simulated demineralized liquid for the remaining 16 hours. And in order to simulate the loss of materials each time brushing teeth, we also set up a daily brushing group. Both groups repeated the above process for 21 days. The above-treated tooth slices were finally tested for the long-term effectiveness of the occlusion using a scanning electron microscope and a blasting device, and the results were Figures 5 and 6 The surface and cross-sectional SEM images of the dentinal tubules in the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules and the dentinal tubules in the experimental group of SF-TA self-assembled hydrogel blocking dentinal tubules and brushing treatment after pH cycling for 21 days are shown in the figure. Specifically, Figure 5 -A1 is the surface SEM image of the dentinal tubules in the SF-TA self-assembled hydrogel blocking dentinal tubules experimental group after pH cycling for 21 days. Figure 5 -A2 is a cross-sectional SEM image of the dentinal tubules in the SF-TA self-assembled hydrogel occluding dentinal tubules experimental group after pH cycling for 21 days; Figure 5 -B1 is the surface SEM image of the dentin tubules blocked by SF-TA self-assembled hydrogel and brushed after pH cycling for 21 days. Figure 5 -B2 is a cross-sectional SEM image of the dentinal tubules blocked by SF-TA self-assembled hydrogel and treated with brushing after pH cycling for 21 days; Figure 6 This is a bar graph of the bursting data of the dentinal tubules in the experimental group with SF-TA self-assembled hydrogel blocking dentinal tubules and the dentinal tubules in the experimental group with SF-TA self-assembled hydrogel blocking dentinal tubules and brushing treatment after pH cycling for 21 days.
[0093] according to Figure 5 It can be seen that the surfaces and cross-sections of the dentin slices treated with SF-TA self-assembled hydrogel and the dentin slices treated with SF-TA self-assembled hydrogel and brushed daily showed good deep and dense occlusion of dentinal tubules.
[0094] according to Figure 6It can be seen that the airtight pressure values of the TA-SF self-assembled hydrogel occluding dentinal tubules experimental group and the TA-SF self-assembled hydrogel treatment and daily brushing group both reached the maximum value of the blasting device, 160KPa.
[0095] 1.5 Improved TDD device to test the cytocompatibility and cytoprotective effect of SF-TA self-assembled hydrogel
[0096] In order to verify the cell compatibility and cell protection effect of SF-TA self-assembled hydrogel, the filter membrane at the bottom of the 24-well Transwell upper chamber was replaced with a dentin sheet with a diameter of 6 mm and a thickness of 1 mm. The acid-etched dentin sheet was used as the control group, and the dentin sheet treated with SF-TA self-assembled hydrogel was used as the experimental group. The filter membrane at the bottom of the Transwell upper chamber was replaced with a titanium sheet with a diameter of 6 mm, thereby simulating the complete isolation of the liquid exchange between the upper and lower chambers of the Transwell, which served as the blank control group. The gap between the dentin sheet or titanium sheet and the Transwell upper chamber was sealed with a flowing resin. A 1% citric acid solution was added to the upper chamber to simulate the stimulation in the oral cavity, and human dental pulp cells were cultured in the lower chamber with full culture medium for 7 days. The cell survival rate and live and dead cell staining were tested at 1, 3, 5, and 7 days, respectively. Figure 7 As shown. Among them, Figure 7 This is a bar graph showing the cell proliferation rate of SF-TA self-assembled hydrogel-treated dentin slices and dental pulp cells after co-culture in the improved TDD device.
[0097] according to Figure 7 It can be seen that the cell compatibility and cell protection effects of SF-TA self-assembled hydrogel were good, with the cell survival rate exceeding 80% on the first day and showing an increasing trend.
[0098] 1.6 Testing the long-term occlusion effect of SF-TA self-assembled hydrogel in rat oral cavity
[0099] The human dentin slice was ground into a size of 4 mm in diameter and 1 mm in thickness, and two small holes were punched in the middle of the tooth slice. Under anesthesia, a stainless steel ligature with a diameter of 0.50 mm was inserted between the incisor and the first and second molars of Sprague–Dawley (SD) rats, and the dentin slice treated with SF-TA self-assembled hydrogel was fixed to the upper jaw of the rat. After 21 days of normal diet, the rat was euthanized and the tooth slice was removed. The removed tooth slice was tested for the long-term effectiveness of the occlusion using a scanning electron microscope, and the microhardness test of the tooth slice was performed. The results were Figures 8 to 9 As shown. Among them, Figure 8 The surface and cross-sectional SEM images of the rat dentinal tubules before and after SF-TA self-assembled hydrogel blocked dentinal tubules. Specifically, Figure 8-A1 is the surface SEM image of the rat dentinal tubules experimental group before SF-TA self-assembled hydrogel blocked the dentinal tubules. Figure 8 -A2 is the cross-sectional SEM image of the rat dentinal tubule experimental group before SF-TA self-assembled hydrogel blocked the dentinal tubules. Figure 8 -B1 is the surface SEM image of the rat dentinal tubules experimental group after SF-TA self-assembled hydrogel blocked the dentinal tubules. Figure 8 -B2 is the cross-sectional SEM image of the rat dentinal tubule experimental group after SF-TA self-assembled hydrogel blocked the dentinal tubules; Fig. 9 The microhardness bar graph of dentin slices treated with SF-TA self-assembled hydrogel after 21 days in the rat oral cavity.
[0100] according to Figure 8 It can be seen that the dentin slices treated with SF-TA self-assembled hydrogel in the real oral cavity of rats for 21 days showed good occlusion of dentinal tubules, indicating that SF-TA self-assembled hydrogel can effectively block dentinal tubules and thus has a long-term effect in treating dentin hypersensitivity.
[0101] according to Fig. 9 It can be seen that after 21 days, the hardness of the dentin slices treated with SF-TA self-assembled hydrogels recovered to the level of normal healthy dentin slices.
[0102] 1.7 Feasibility of testing the desensitization of SF-TA self-assembled hydrogel on rabbit teeth
[0103] Three 12-week-old male New Zealand rabbits weighing approximately 2.1-2.5 kg were selected. Under anesthesia, a fast-acting handpiece was used to remove the enamel on the surface of the upper and lower incisors to expose the dentin, and 37% phosphoric acid gel was used to etch and expose the dentinal tubules to simulate dentin hypersensitivity. After the surface of the maxillary incisor was blown dry, 10% SF solution was first added. After the surface was air-dried, 10% TA solution was added and air-dried again. The mandibular incisor served as the control group. The rabbits were euthanized and the upper and lower incisors were extracted. The SF-TA self-assembled hydrogel remaining on the surface was brushed off with an electric toothbrush. The microscopic morphology of the tooth surface and cross-section of the obtained rabbit teeth was observed using a scanning electron microscope, and the results were as follows: Fig.10 As shown. Among them, Fig.10 The surface and cross-sectional SEM images of dentinal tubules before and after the use of SF-TA self-assembled hydrogel in rabbit teeth. Specifically, Fig.10 -A1 is the SEM image of the dentin tubule surface of SF-TA self-assembled hydrogel before being used in rabbit teeth. Fig.10 -A2 is a SEM image of the dentin tubule cross section of the SF-TA self-assembled hydrogel before use in rabbit teeth. Fig.10 -B1 is the SEM image of the dentin tubule surface after SF-TA self-assembled hydrogel was used in rabbit teeth. Fig.10 -B2 is the SEM image of the cross section of dentinal tubules after the SF-TA self-assembled hydrogel was used in rabbit teeth.
[0104] according to Fig.10 It can be seen that within 1 hour, SF-TA self-assembled hydrogel can achieve dense occlusion in dentinal tubules. This is the first time that SF-TA self-assembled hydrogel has been used to treat dentin hypersensitivity in living rabbits, which further shows that SF-TA self-assembled hydrogel has clinical significance in occluding dentinal tubules to treat dentin hypersensitivity.
[0105] Example 2
[0106] This embodiment provides the application of PVA-TA self-assembled hydrogel, specifically including:
[0107] Preparation of S201-TA solution
[0108] Add 10 g of tannic acid (TA) powder into 90 g of deionized water, stir to dissolve, and obtain a 10% TA solution for later use;
[0109] Preparation of S202-PVA solution
[0110] 5 g of polyvinyl alcohol (PVA) powder with a molecular weight of 9000-10000 Da was added to 95 g of deionized water and dispersed, and then the temperature was raised to 95° C. and heated and stirred for 2 h to dissolve to obtain a PVA solution with a mass fraction of 15%, which was set aside;
[0111] S203-Simulation of dentin hypersensitivity
[0112] The dentin part of the excised tooth was cut with a tooth cutter in a direction perpendicular to the long axis of the tooth to obtain a dentin slice with a thickness of about 1 mm, which was gradually polished with 600-3000# sandpaper and then washed with deionized water. Then, 17% EDTA with pH=7 was used for acid etching for 8 minutes to expose the dentinal tubules, and then immersed in deionized water for ultrasonication 3 times, each time for 5 minutes.
[0113] S204-Oil sealing treatment for dentin hypersensitivity
[0114] After drying the dentin slice with nitrogen, the PVA solution was first added to the dentin slice and air-dried for about 30 minutes, and then the TA solution was added to the surface of the dentin slice and air-dried again. Finally, the residue on the surface of the dentin slice was cleaned with an electric toothbrush.
[0115] In order to verify the technical effect of Example 2, the dentin treated with PVA-TA self-assembled hydrogel was subjected to structural characterization and performance testing, as follows:
[0116] 2.1 Characterization of dentin surface and cross-section morphology
[0117] After the dentin slices treated with PVA-TA self-assembled hydrogel and the dentin slices brittlely fractured by liquid nitrogen were dried in a drying box overnight, the microscopic morphology of the surface and cross-section of the dentin slices was characterized using a scanning electron microscope (accelerating voltage of 10.00 kV). Fig.11 As shown. Among them, Fig.11 Surface and cross-sectional SEM images of the blank group simulating dentin hypersensitivity and the experimental group of PVA-TA self-assembled hydrogel blocking dentinal tubules.
[0118] according to Fig.11 It can be seen that the dentin sheets treated with PVA-TA self-assembled hydrogel formed a tight occlusion of the dentinal tubules.
[0119] 2.2 Explosion test to test the dentin sealing performance
[0120] The sealing performance of PVA-TA self-assembled hydrogel on dentin slices with dentin hypersensitivity was tested by using a blasting device, namely: first, the dentin slice treated with PVA-TA self-assembled hydrogel was clamped between a pair of rubber rings with a central opening and fixed in the device. Secondly, when the gas passes through, the water droplets will move in the tube, and the critical air pressure is recorded at this time. In order to simulate the effects of friction and acid etching in the oral environment, the dentin slice was subjected to a second blasting experiment after mechanical friction treatment; finally, the dentin slice was placed in a 2% EDTA aqueous solution for acid etching for 2 minutes, and the sealing performance was tested for the third time using the blasting device. The results Fig.12 As shown. Among them, Fig.12 A bar graph showing the bursting data of PVA-TA self-assembled hydrogel blocking dentin tubules.
[0121] according to Fig.12 It can be seen that the airtight pressure value treated with the PVA-TA self-assembled hydrogel desensitizer can reach the maximum value of the blasting device, 160 kPa, and does not decrease after mechanical friction and acid etching, maintaining a good sealing state.
[0122] Example 3
[0123] This embodiment provides a method for preparing a PVP-TA self-assembled hydrogel, which specifically comprises the following steps:
[0124] Preparation of S301-TA solution
[0125] Add 10 g of tannic acid (TA) powder into 100 g of deionized water, stir to dissolve, and obtain a 10% TA solution for later use;
[0126] Preparation of S302-PVP solution
[0127] 10 g of polyvinyl pyrrolidone (PVP) powder with a molecular weight of k30 was added to 90 g of deionized water and dispersed, then the temperature was raised to 80° C., and heated and stirred for 2 h to dissolve to obtain a PVP solution with a mass fraction of 10%, which was set aside;
[0128] S303-Simulation of dentin hypersensitivity
[0129] The dentin part of the excised tooth was cut with a tooth cutter in a direction perpendicular to the long axis of the tooth to obtain a dentin slice with a thickness of about 1 mm, which was gradually polished with 600-3000# sandpaper and then washed with deionized water. Then, 17% EDTA with pH=7 was used for acid etching for 8 minutes to expose the dentinal tubules, and then immersed in deionized water for ultrasonication 3 times, each time for 5 minutes.
[0130] S304-Oil sealing treatment of dentin hypersensitivity
[0131] After drying the dentin slice with nitrogen, the PVP solution was first added to the dentin slice and air-dried for about 30 minutes, and then the TA solution was added to the surface of the dentin slice and air-dried again. Finally, the residue on the surface of the dentin slice was cleaned with an electric toothbrush.
[0132] In order to verify the technical effect of Example 3, the dentin treated with PVP-TA self-assembled hydrogel was subjected to performance tests, as follows:
[0133] The sealing performance of PVP-TA self-assembled hydrogel on dentin slices with dentin hypersensitivity was tested by using a blasting device: first, the dentin slice treated with PVP-TA self-assembled hydrogel was sandwiched between a pair of rubber rings with a central hole and fixed in the device; secondly, when the gas passed through, the water droplets would move in the tube, and the critical gas pressure was recorded at this time. In order to simulate the effects of friction and acid etching in the oral environment, the dentin slice was subjected to mechanical friction treatment and then subjected to a second blasting experiment; finally, the dentin slice was placed in a 2% EDTA aqueous solution for acid etching for 2 minutes, and the sealing performance was tested by the blasting device for the third time. The results were Fig.13 As shown. Among them, Fig.13 This is a bar graph showing the bursting data of PVP-TA self-assembled hydrogel blocking dentin tubules.
[0134] according to Fig.13 It can be seen that the airtight pressure value treated with PVP-TA self-assembled hydrogel can reach the maximum value of 160kPa of the blasting device, and it does not decrease after mechanical friction and acid etching, maintaining a good sealing state.
[0135] Example 4
[0136] This embodiment provides the application of PVA-GA self-assembled hydrogel, specifically including:
[0137] Preparation of S401-GA solution
[0138] 10 g of gallic acid (GA) powder was added to 90 g of deionized water and dispersed, then the temperature was raised to 90° C., and heated and stirred to dissolve to obtain a GA solution with a mass fraction of 10%, which was set aside;
[0139] Preparation of S402-PVA solution
[0140] 5 g of polyvinyl alcohol (PVA) powder with a molecular weight of 9000-10000 Da was added to 95 g of deionized water and dispersed, and then the temperature was raised to 95° C. and heated and stirred for 2 h to dissolve to obtain a PVA solution with a mass fraction of 15%, which was set aside;
[0141] S403-Simulation of dentin hypersensitivity
[0142] The dentin part of the excised tooth was cut with a tooth cutter in a direction perpendicular to the long axis of the tooth to obtain a dentin slice with a thickness of about 1 mm, which was gradually polished with 600-3000# sandpaper and then washed with deionized water. Then, 17% EDTA with pH=7 was used for acid etching for 8 minutes to expose the dentinal tubules, and then immersed in deionized water for ultrasonication 3 times, each time for 5 minutes.
[0143] S404-Oil sealing treatment of dentin hypersensitivity
[0144] After drying the dentin slice with nitrogen, the PVA solution was first added to the dentin slice and air-dried for about 30 minutes, and then the GA solution was added to the surface of the dentin slice and air-dried again. Finally, the residue on the surface of the dentin slice was cleaned with an electric toothbrush.
[0145] In order to verify the technical effect of Example 4, the dentin treated with PVA-GA self-assembled hydrogel was subjected to performance tests, as follows:
[0146] The sealing performance of PVA-GA self-assembled hydrogel on dentin slices with dentin hypersensitivity was tested by using a blasting device: first, the dentin slice treated with PVA-GA self-assembled hydrogel was sandwiched between a pair of rubber rings with a central opening and fixed in the device. Secondly, when the gas passes through, the water droplets will move in the tube, and the critical air pressure is recorded at this time. In order to simulate the effects of friction and acid etching in the oral environment, the dentin slice was subjected to a second blasting experiment after mechanical friction treatment; finally, the dentin slice was placed in a 2% EDTA aqueous solution for acid etching for 2 minutes, and the sealing performance was tested for the third time using the blasting device. The results Fig.14 As shown. Among them, Fig.14 The bar graph shows the bursting data of PVA-GA self-assembled hydrogel blocking dentin tubules.
[0147] according to Fig.14 It can be seen that the airtight pressure value treated with the PVA-GA self-assembled hydrogel desensitizer can reach the highest value of the blasting device, 160 kPa, and does not decrease after mechanical friction and acid etching, maintaining a good sealing state.
[0148] Example 5
[0149] This embodiment provides a method for preparing a PVP-GA self-assembled hydrogel, which specifically comprises the following steps:
[0150] Preparation of S501-TA solution
[0151] 10 g of gallic acid (GA) powder was added to 90 g of deionized water and dispersed, then the temperature was raised to 90° C., and heated and stirred to dissolve to obtain a GA solution with a mass fraction of 10%, which was set aside;
[0152] Preparation of S502-PVP solution
[0153] 10 g of polyvinyl pyrrolidone (PVP) powder with a molecular weight of k30 was added to 90 g of deionized water and dispersed, then the temperature was raised to 80° C., and heated and stirred for 2 h to dissolve to obtain a PVP solution with a mass fraction of 10%, which was set aside;
[0154] S503-Simulation of dentin hypersensitivity
[0155] The dentin part of the excised tooth was cut with a tooth cutter in a direction perpendicular to the long axis of the tooth to obtain a dentin slice with a thickness of about 1 mm, which was gradually polished with 600-3000# sandpaper and then washed with deionized water. Then, 17% EDTA with pH=7 was used for acid etching for 8 minutes to expose the dentinal tubules, and then immersed in deionized water for ultrasonication 3 times, each time for 5 minutes.
[0156] S504-Oil sealing treatment for dentin hypersensitivity
[0157] After drying the dentin slice with nitrogen, the PVP solution was first added to the dentin slice and air-dried for about 30 minutes, and then the TA solution was added to the surface of the dentin slice and air-dried again. Finally, the residue on the surface of the dentin slice was cleaned with an electric toothbrush.
[0158] In order to verify the technical effect of Example 5, the dentin treated with PVP-GA self-assembled hydrogel was subjected to performance tests, as follows:
[0159] The sealing performance of PVP-GA self-assembled hydrogel on dentin slices with dentin hypersensitivity was tested by using a blasting device: first, the dentin slice treated with PVP-GA self-assembled hydrogel was sandwiched between a pair of rubber rings with a central hole and fixed in the device; secondly, when the gas passed through, the water droplets would move in the tube, and the critical gas pressure was recorded at this time. In order to simulate the effects of friction and acid etching in the oral environment, the dentin slice was subjected to mechanical friction treatment and then subjected to a second blasting experiment; finally, the dentin slice was placed in a 2% EDTA aqueous solution for acid etching for 2 minutes, and the sealing performance was tested by the blasting device for the third time. The results were as follows: Fig.15 As shown. Among them, Fig.15 The bar graph shows the bursting data of PVP-GA self-assembled hydrogel blocking dentin tubules.
[0160] according to Fig.15 It can be seen that the airtight pressure value treated with PVP-GA self-assembled hydrogel can reach the highest value of 160 kPa of the blasting device, and it does not decrease after mechanical friction and acid etching, maintaining a good sealing state.
[0161] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0162] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A desensitizing agent for treating dentin hypersensitivity, characterized in that: The desensitizing therapeutic agent for dentin hypersensitivity contains a self-assembling hydrogel; The self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution; The macromolecular solution and the polyphenol solution are applied to the hypersensitive dentin surface in sequence; The macromolecular compound in the macromolecular solution is silk fibroin; The polyphenol in the polyphenol solution is tannic acid.
2. The desensitizing agent for dentin hypersensitivity according to claim 1, characterized in that When the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is (0.5-15):
1.
3. A use of a self-assembled hydrogel, characterized in that: Use of the self-assembled hydrogel for preparing a hypersensitive dentinal tubule plugging agent; Wherein, the self-assembled hydrogel is formed by contacting a 1-30% w / w macromolecular solution with a 1-30% w / w polyphenol solution; The macromolecular solution and the polyphenol solution are applied to the hypersensitive dentin surface in sequence; The macromolecular compound in the macromolecular solution is silk fibroin; the polyphenol in the polyphenol solution is tannic acid.
4. The use according to claim 3, characterized in that When the macromolecular solution is in contact with the polyphenol solution, the mass ratio of the macromolecular solution to the polyphenol solution is (0.5-15):1.
Citation Information
Patent Citations
Polyphenols / peg based hydrogel system for dental varnish
CN110505864A
Method for preparing injectable polyphenol-macromolecule adhesive hydrogel
CN115651218A
Dental varnish
US20220378668A1